ON TRENDS IN THE DEVELOPMENT OF MILITARY OPERATIONS IN MODERN MILITARY CONFLICTS (American Journal of Research in Humanities and Social Sciences, 2023)
In article on the base of analysis main facts of the environment, determined new form and methods of the conduct defense. Defined the problem questions, determined basic confrontation, suggested the ways to their solutions.